2012
DOI: 10.1016/j.ijrobp.2011.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemoradiotherapy Improves Survival in Patients With Hypopharyngeal Cancer

Abstract: Purpose To retrospectively review our institutional experience with hypopharyngeal carcinoma with respect to treatment modality. Methods and Materials A total of 70 patients with hypopharyngeal cancer treated between 1999 and 2009 were analyzed for functional and survival outcomes. The treatments included surgery alone (n = 5), surgery followed by radiotherapy (RT) (n = 3), surgery followed by chemoradiotherapy (CRT) (n = 13), RT alone (n = 2), CRT alone (n = 22), induction chemotherapy followed by RT (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Paximadis et al 34 reported on 70 sequential patients, assessing the effectiveness of ccrt as primary treatment (or when added to other regimens) compared with primary surgery or induction ccrt (57 patients received ccrt, 13 received another treatment). Those authors acknowledged that the ccrt group was younger, but the report made no mention of comorbid illness.…”
Section: Discussionmentioning
confidence: 99%
“…Paximadis et al 34 reported on 70 sequential patients, assessing the effectiveness of ccrt as primary treatment (or when added to other regimens) compared with primary surgery or induction ccrt (57 patients received ccrt, 13 received another treatment). Those authors acknowledged that the ccrt group was younger, but the report made no mention of comorbid illness.…”
Section: Discussionmentioning
confidence: 99%
“…Reports describing the 3-year survival rate of hypopharyngeal cancer that reconstruct by flap after resection are scarce. Paximadis reported a total of 70 patients with hypopharyngeal cancer treated by surgery, radiotherapy, chemotherapy or combined between 1999 and 2009 [17]. The 3-year survival rate for stage I-IVa (resectable) patients was 60 %.…”
Section: Discussionmentioning
confidence: 99%
“…The follow‐up for this group of patients is similar to that described previously . Briefly, upon completion of therapy, patients were seen on a monthly basis for the first year, every 2 to 3 months in the second year, every 3 to 6 months in years 3 through 5, and yearly thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…The follow-up for this group of patients is similar to that described previously. 19 Briefly, upon completion of therapy, patients were seen on a monthly basis for the first year, every 2 to 3 months in the second year, every 3 to 6 months in years 3 through 5, and yearly thereafter. Follow-up evaluations consisted of a comprehensive medical history and physical examination, which included flexible laryngoscopy.…”
Section: Follow-upmentioning
confidence: 99%